Architecture and Theology : The Art of Place - Rae, Murray (Book collections on Project MUSE., 2017)
The dynamic relationship between art and theology continues to fascinate and to challenge, especially when theology addresses art in all of its variety. In 'Architecture and Theology: The Art of Place', author Murray Rae turns to the spatial arts, especially architecture, to investigate how the art forms engaged in the construction of our built environment relate to Christian faith. Rae does not offer a theology of the spatial arts, but instead engages in a sustained theological conversation with the spatial arts. Because the spatial arts are public, visual, and communal, they wield an immense but easily overlooked influence. 'Architecture and Theology' overcomes this inattention by offering new ways of thinking about the theological importance of space and place in the experience of God, the relation between freedom and law in Christian life, the transformation involved in God's promised new creation, biblical anticipation of the heavenly city, divine presence and absence, the architecture of repentance and remorse, and the relation between space and time. In doing so, Rae finds an ample place for theology amidst the architectural arts.